2017
DOI: 10.1111/wrr.12526
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pH on cell viability, cell migration, cell proliferation, wound closure, and wound reepithelialization: In vitro and in vivo study

Abstract: Wound microenvironment plays a major role in the process of wound healing. It contains various external and internal factors that participate in wound pathophysiology. The pH is an important factor that influences wound healing by changing throughout the healing process. Several previous studies have investigated the role of pH in relation to pathogens but studies concentrating on the effects of pH on wound healing itself are inconclusive. The purpose of this study was to comprehensively and in a controlled fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
111
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 173 publications
(125 citation statements)
references
References 31 publications
(56 reference statements)
5
111
0
Order By: Relevance
“…However, it must also be considered that cytotoxic proteins such as LL37, as mentioned above, are also present in saliva, indicating that a delicate balance exists between mitogens and antimicrobial proteins (Boink et al, 2017). It has been shown that a prolonged acidic wound environment can prevent wound closure and re-epithelialization (Kruse et al, 2017). Even though pH values of saliva can differ between donors, pooled saliva results in batches within the pH range (6.5 to 8.5) that have been shown to be welltolerated for keratinocyte proliferation (Sharpe, Harris, Jubin, Bainbridge, & Jordan, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…However, it must also be considered that cytotoxic proteins such as LL37, as mentioned above, are also present in saliva, indicating that a delicate balance exists between mitogens and antimicrobial proteins (Boink et al, 2017). It has been shown that a prolonged acidic wound environment can prevent wound closure and re-epithelialization (Kruse et al, 2017). Even though pH values of saliva can differ between donors, pooled saliva results in batches within the pH range (6.5 to 8.5) that have been shown to be welltolerated for keratinocyte proliferation (Sharpe, Harris, Jubin, Bainbridge, & Jordan, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Although the pH did increase with the increase of particle concentrations, the pH did not vary over a wide range, and stayed between 7.4 and 9.1. 27,28 Just based on the pH changes alone, cells should have proliferated more at low particle concentrations due to slight pH increase (pH up to 8.0), compared to control. Although Mg-Ti sacrificed more cells than Mg, there was no difference in pH measurements between Mg and Mg-Ti.…”
Section: Figure 10mentioning
confidence: 99%
“…In contradiction to the animal and clinical studies, Kruse et al have shown using titanium chambers implanted in rats that contain culture medium buffered at different pH, which prolonged exposure of the wound to an acidic environment prevents wound closure and re‐epithelialization, whereas an alkaline environment did not have a negative impact on wound closure or re‐epithelialization when compared to physiological pH. This suggests that a temporary exposure to acidic conditions is more beneficial to heeling than full time exposure and that on a term exposure to an alkaline pH (8.5) would be beneficial for wound healing.…”
Section: Protons and Hydroxide Ions: Phmentioning
confidence: 97%
“…It as demonstrate in an in vitro scratch wound model that a pH increase from 7.4 to 8.4 causes a decrease in fibroblast proliferation and migration . In contrast, it was shown that alkaline pH (pH = 8.5) could increase proliferation while decreasing the migration . pH also affects keratinocyte behavior; it has been shown that lowering the pH was deleterious to the cells for both proliferation and migration .…”
Section: Protons and Hydroxide Ions: Phmentioning
confidence: 99%
See 1 more Smart Citation